Potentials of pure xenograft materials in maxillary ridge augmentation: A case series - Mehrdad Lotfazar; Reza Amid; Anahita Moscowchi (Elsevier, 2024)
Many patients require edentulous ridge augmentation for dental implant placement. The main objective of this study was to evaluate the results of maxillary edentulous ridge augmentation exclusively with xenograft materials with and without simultaneous sinus floor elevation. This study reports the data retrieved from the records of 16 patients. The treatment outcome was assessed at least 6 months, postoperatively. Paired samples t-test or Wilcoxon Signed Rank test was used to compare the pre-and postoperative ridge dimensions. Dental implants were placed simultaneously in 7 patients, while 9 patients underwent delayed implant placement. In total, 68 implants were placed, and 12 patients also underwent maxillary sinus floor augmentation. A significant bone gain was achieved in both horizontal and vertical dimensions of edentulous maxillary ridges (P < 0.001). Ridge width increased by an average of 4.35 ± 1.90 mm (95% CI: 3.84 to 4.85 mm) while ridge height in areas of sinus floor augmentation increased by 8.19 ± 2.91 mm (95% CI: 7.33 to 9.05 mm). Within the study limitations, it appears that maxillary ridge augmentation according to the guided bone regeneration (GBR) protocols with exclusive use of xenograft particulate materials can provide optimal bone quantity for dental implant placement.